KONTRIBUSI KOMPETENSI PROFESIONAL DALAM MENINGKATKAN KINERJA GURU - Firman Yudhanegara (Pascasarjana Unviersitas Majalengka, 2019)
The research is motivated by the phenomenon of low teacher performance, aimed at knowing and analyzing the contribution of professional competence to teacher performance. The method used is a survey with descriptive and verification analysis. The population and sample of the study consisted of PAI SMP and MTs teachers in Sukahaji District, with the main questionnaire data collection tool. The results showed descriptively the variables of professional competence and teacher performance were in good condition, but there were weaknesses in certain aspects. By verification professional competence has a significant effect on teacher performance with a magnitude of influence of 69.72%. In conclusion, professional competence can improve teacher performance.